METHODS OF STRENGTHENING CREATIVITY THINKING IN TEACHERS - Oraqbaev Zulkander Zinatdinovich (Galaxy International Interdisciplinary Research Journal, 2024)
In today’s fast-evolving educational landscape, fostering creativity in teachers is essential to promote dynamic and effective learning environments. This paper explores strategies for enhancing creative thinking in teachers, addressing theoretical frameworks and practical methods. By examining existing literature, practical methods, and real-world applications, this article provides insights into how teachers can develop and sustain creative thinking in their teaching practice, ultimately enhancing student engagement and learning outcomes.